2017
DOI: 10.1055/s-0043-122743
|View full text |Cite
|
Sign up to set email alerts
|

Video-Kopfimpulstest: geringer Nutzen zur Unterscheidung peripherer und zentraler Schwindel

Abstract: In this study V-HIT showed little diagnostic use, especially in separating peripheral from central disease. The lacking correlation between asymmetry in caloric testing and asymmetry of V-HIT gain challenges current pathophysiological concepts of impaired VOR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
1
1
0
1
Order By: Relevance
“…Similar to previous studies, cases with conspicuous values were identified in the caloric test, while the vHIT gain parameter was in the physiological range, although both tests measure the function of the hSCC (38). Blödow et al (52) assumed that, in the case of peripheral vestibulopathy, as suspected after implantation, the caloric irrigation test would show conspicuous values more frequently than vHIT.…”
Section: Video Head Impulse Testsupporting
confidence: 73%
See 1 more Smart Citation
“…Similar to previous studies, cases with conspicuous values were identified in the caloric test, while the vHIT gain parameter was in the physiological range, although both tests measure the function of the hSCC (38). Blödow et al (52) assumed that, in the case of peripheral vestibulopathy, as suspected after implantation, the caloric irrigation test would show conspicuous values more frequently than vHIT.…”
Section: Video Head Impulse Testsupporting
confidence: 73%
“…However, we found no association of catch-up saccades with the occurrence of vertigo. Patscheke et al (38) analyzed the occurrence of vHIT catch-up saccades in 171 patients suffering from vertigo and showed that the sensitivity of the vHIT for detecting a peripheral-vestibular disorder was low and that the two (peripheral) parameters "gain" and "catch-up saccades"contrary to expectations-were only conspicuous to a small extent (22%) in the same patients.…”
Section: Video Head Impulse Testmentioning
confidence: 99%
“…Die erste Originalarbeit der Giessener Kolleginnen und Kollegen untersucht die Wertigkeit insbesondere des Gains des Video-Kopfimpulstests zur sicheren Diagnose einer peripher-vestibulären Störung [8]. Die Autoren schlussfolgern, dass die Unterscheidung einer bedrohlichen zentralen Erkrankung von einer Erkrankung des Labyrinths beim klinischen Bedside-Test in der Kombination mit der Nystagmusprüfung unter der Frenzelbrille und der vertikalen Achsenabweichung der Augen mit hoher Sicherheit möglich ist, dies durch die alleinige Auswertung des V-KIT in horizontaler Ausrichtung aber nicht gelingt.…”
Section: Sehr Geehrte Kolleginnen Und Kollegenunclassified